THE PRESSURE OF TECHNOLOGICAL INNOVATIONS IN MEETING AND EVENT INDUSTRY UNDER THE COVID-19 INFLUENCE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The innovation in technologies is one of the principal external forces that has a direct influence on the competitiveness of the meeting and the event industry. Therefore, implementation and adaptation of the new technological solutions in it has continuously followed the innovations in technological industry itself. However, the COVID-19 pandemic with the following lockdowns has pushed the industry to search for new technological alternatives to innovate their way out of the crisis in a very short time period. This was the first time when all the events from small family celebrations and weddings up to the international conferences and product launch events, have had to be cancelled or postponed or could have happened only to a very limited extent and under strict regulations excluding any larger gatherings of people. The event providers were forced to find new solutions to continue their business and not to hibernate with the minimum downtime allowance granted by the state to the employees. Technologies supporting various types of online events became the ultimate digital tool that helped event planners to execute projects from the beginning to the end after March 2020. The purpose of the research is to explore these changes in the usage of the technologies in meetings and events organized in Latvia caused by COVID-19. The quantitative analysis of the structural on-line survey data provides insights on what extent technology adoption in meetings and events businesses has been before and during COVID-19 and what are the future prospects supplemented by the in-depth interview data and qualitative analysis. Authors are investigating what is the amount of virtual and hybrid events organized in Latvia before and after COVID-19, what platforms the organizers used for their virtual events, what is the level of satisfaction and what kind of challenges the event organizers faced in the process of adoption of new technologies. The results of this research not only state the current position within the framework of the industry, but also enriches discussion about the adoption of new technologies to innovate the way out of the crisis and could help in some degree to strengthen the productivity growth in a long term perspective.